Multiwideband Bandpass Filter Based on Folded Quad Cross-Stub Stepped Impedance Resonator - Gunawan Wibisono; Teguh Firmansyah; Herudin Herudin; Muh Wildan; Toto Supriyanto; Mudrik Alaydrus; Febrizal Ujang (International Journal of Antennas and Propagation)
A multiwideband bandpass filter (MW-BPF) using a quad cross-stub stepped impedance resonator (QC-SSIR) was simulated, fabricated, and measured. The proposed QC-SSIR is designed on a four-series arrangement of crossed open stub (COS) structures where each open stub is developed with a step impedance resonator (SIR) structure to generate a wide bandwidth. Compared to the COS resonator, the QC-SSIR has a wider fractional bandwidth and good transmission coefficients and is compact. ABCD matrix analysis is used to investigate the filter structure. Furthermore, the MW-BPF is designed on an FR4 microstrip substrate with εr = 4.4, thickness h = 1.6 mm, and tan δ = 0.0265. The results show that the proposed MW-BPF using a QC-SSIR achieves transmission coefficients/fractional bandwidths of −0.60 dB/49.3%, −1.49 dB/18.7%, and −1.93 dB/13.9% at 0.81 GHz, 1.71 GHz, and 2.58 GHz, respectively. Furthermore, to reduce the filter size, a folded QC-SSIR (FQC-SSIR) structure was also proposed. The results show that the proposed MW-BPF using an FQC-SSIR achieves transmission coefficients/fractional bandwidths of −0.57 dB/49.6%, −1.21 dB/17.7%, and −1.76 dB/12.5% at 0.82 GHz, 1.80 GHz, and 2.62 GHz, respectively. The size of the proposed MW-BPF using an FQC-SSIR is reduced by up to 46% compared with the MW-BPF using a QC-SSIR. Finally, the performance of the simulated MW-BPF based on the QC-SSIR and FQC-SSIR was in good agreement with the measurement results.